Regulation of the solid household wastes generation and treatment in Ukraine: guidelines and priorities - Garkushenko, O.N. (Економіка промисловості, 2014)
Accumulation of solid household wastes and rates of their growth in the world as a whole and in Ukraine - in particular caused the raise of concerns among population. One of the reasons of this situation is that solid household wastes represent the irrational use of scarce natural resources. In addition to this wastes accumulation on landfills or their incineration causes pollution, which may result in the increase of morbidity rate. In the developed countries of the world measures on the regulation of solid household wastes generation and treatment are undertaken for about 30 years. Due to this new approaches of wastes treatment were developed as well as new types of packaging - one of the main compounds of the solid household wastes in the modern world. In the meantime recycling and reuse of scrap are the most preferred ways of waste treatment in leading countries of the world. That allows to use same materials for several times without extraction of raw materials as well as it saves space on landfills. Pollution of air and groundwaters is decreasing in turn. But in Ukraine the situation with regulation of solid household wastes is quite opposite. There are a lot of overloaded landfills and dumps. Most part of that landfills as well as incineration plants does not correspond to the ecological safety requirements. Ukrainian legislation on the wastes treatment is far from perfect. Taking into account all of the preceding it was assumed that to improve situation in Ukraine it would be useful to analyze the experience of leading countries in the field of the regulation of wastes generation and treatment. As long as Germany is a world leader in this field and industrial enterprises are directly engaged in the process of diminishing volumes of solid household wastes and their further recycling there this country appears to be a good example for that matter. On the ground of the presented in the paper German experience of the regulation of solid household wastes treatment as well as account of economic, institutional, environmental and some other peculiarities of Ukraine recommendations on the improvement of regulation of solid household wastesgeneration and treatment was offered.